Destination Image as Means of Branding and Marketing: Evidence from a Mountainous City Destination in Greece - Moustaka, Argyri; Constantoglou, Mary (Journal of Tourism Management Research, 2021)
The purpose of this paper is to offer insights on a mountainous city destination branding and image. The paper reviews existing literature by analyzing its factors, its formation and its measurement elements. The study aims to test a theoretical model of destination branding by examining the relationships of cognitive, affective and unique image components with the overall brand image and the tourist’s behavior in the city of Edessa on the mountainous area of Pella in Greece. This paper contributes to the analysis and exploration of tourists' views on the image of Edessa in such a way as to assist managers and tourism professionals in reviewing their marketing and promotional activities to meet the needs of tourists. The methodology used was twofold. First a quantitative research to the city’s tourists was conducted and secondly a qualitative research with the use of interviews was conducted to the city’s stakeholders. Focus was given on the general characteristics of the city of Edessa including the vision, goals, actions, set by the city authorities, in order to extract results through the research based on how the image of Edessa is perceived by the visitors and residents of the city and especially the stakeholders and those whose decisions shape the touristic image of the place. The results of the research conducted shows that the creation of images is related to the significance of the water element through the breathtaking waterfalls and city’s natural environment. In addition, the agricultural products of the area, contribute to the enhancement of the image of the city and particularly the integration of fruits in the local gastronomical culture.